Performance of sugar palm fibre-reinforced vinyl ester composites at different fibre arrangements - Ishak, Muhammad Ammar (2017)
Natural fibre reinforced composites have gained their significance in engineering because of green material. Plus, it have tolerable strength and stiffness, ease to access, lightweight, ease of detach, support energy recovery, good toughness, low density, low price and biodegradable. Although sugar palm fibre has been studied by many scholars for more than a decade as reinforcement in composites, there is no work reported in the literature on using the vinyl ester (VE) as matrix in the sugar palm fibre composites. Hence, a study on performance of sugar palm fibre reinforced VE composites is discussed in this thesis. The goal of this study is to determine the effect of different fibre arrangements on mechanical, water absorption and morphological properties of long sugar palm fibre reinforced VE composites. Hand lay-up method was used while preparing the composites. VE was mixed with untreated long sugar palm fibres in a mould at three types of arrangements which were unidirectional, 0°/90° woven, and ±45° woven; and left for curing. Test samples were cut from the composites and were tested for mechanical properties (tensile, flexural and impact test) and water absorption. Some fractured specimens from the impact test were investigated under scanning electron microscope (SEM) to study the interface between fibre and matrix. Results showed unidirectional gained excellent performance in tensile modulus, flexural strength, flexural modulus, impact strength, and water absorption with value of 2501 MPa, 93.08 MPa, 3328 MPa, 33.66 kJ/m2, and 0.32 %, respectively. Only tensile strength was led by ±45° woven (15.67 MPa). Therefore, unidirectional is the best fibre arrangement for sugar palm fibre reinforced VE composites compared with arrangement of 0°/90° woven, and ±45° woven due to have consistent results through all tests, and can be proposed as material in useful application such as automotive applications.